Variation in desiccation tolerance among papaya accessions (Carica papaya L.) and its implications for conservation in germplasm banks (Research, Society and Development, 2026)
Seed conservation in germplasm banks depends on maintaining viability over time, and desiccation tolerance is a key factor determining storage success, particularly in tropical species such as papaya (Carica papaya L.). However, information on the variability of this trait among different accessions remains limited, hindering the development of efficient long-term conservation strategies. Therefore, this study aimed to evaluate desiccation tolerance in papaya accessions from the Active Germplasm Bank of Embrapa Cassava and Fruits. The experiment was conducted in a completely randomized design. Initially, seed moisture content and germination were determined. Subsequently, seeds were subjected to drying conditions (silica gel) and moist storage (vermiculite), both in hermetically sealed containers. Of the 17 accessions evaluated, 12 (70.6%) were classified as desiccation tolerant, while 5 (29.4%) were sensitive. The results reveal significant intraspecific variation, with a strong genotype effect on desiccation response. These findings highlight the need for accession-specific conservation strategies to ensure long-term seed viability.